Degradation Processes in the Contact Layers of Forming Tools - Hruby, Jiri; Schindlerova, Vladimira; Rentka, Josef (Manufacturing Technology Journal, 2015)
The article deals with cyclical abrasive wear of the surface of forming tools. At this stage the research focused on the genesis of stress in the contact between a deformed material and a tool in the cold bulk forming process. The experiments were conducted in the simple configuration of the upsetting test. The article presents the results of abrasive wear by a combination of materials of examined samples and upsetting plates. The abrasive wear in the used material specimens was analysed comparatively in the form of the wear factor by the finite element method. Two intersecting phenomenological fields represent the output for the examined material combinations. Firstly, it is a formulation of the dependencies of the maximum depth increase of the surface wear. The argument is the number of exposure cycles. At the same time, the topology of degradations and the resulting roughness in the space of the exposed surface were examined.
Keywords: Cyclical Abrasive Wear; Wear Factor; Roughness; Wear Depth